2018
DOI: 10.1080/14729679.2018.1488147
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of online training for improving camp staff competency

Abstract: Preparing competent staff is a critical issue within the camp community. This quasi-experimental study examined the effectiveness of an online course for improving staff competency in camp healthcare practices among college-aged camp staff and a comparison group (N = 55). We hypothesized that working in camp would increase competency test scores due to opportunities for staff to experientially apply knowledge learned online. Hierarchical linear modeling was used to analyse the cross-level effects of a between-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Research suggests that content knowledge with links to real world contexts, instructional methods, and knowledge about accessible resources are important criteria for designing effective PD for educators (Glazier et al, 2017; Melber & Cox-Petersen, 2005; O'Sullivan et al, 2008). EWBPD is grounded in experiential learning theory (ELT), which assumes that learning is grounded in an iterative process of experience, reflection, experimentation, and integration that creates new knowledge (Garst et al, 2019; Kolb, 2014; Kolb & Kolb, 2009). Figure 1 is a visual representation of the experiential learning process involved in transferring acquired knowledge to new contexts for improved classroom practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research suggests that content knowledge with links to real world contexts, instructional methods, and knowledge about accessible resources are important criteria for designing effective PD for educators (Glazier et al, 2017; Melber & Cox-Petersen, 2005; O'Sullivan et al, 2008). EWBPD is grounded in experiential learning theory (ELT), which assumes that learning is grounded in an iterative process of experience, reflection, experimentation, and integration that creates new knowledge (Garst et al, 2019; Kolb, 2014; Kolb & Kolb, 2009). Figure 1 is a visual representation of the experiential learning process involved in transferring acquired knowledge to new contexts for improved classroom practices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in a longitudinal study of camp-related injuries and illnesses, the American Camp Association (2011) found that during one of the reporting years, 25% of staff injuries occurred between the fifth and seventh day of a camp session (with 50% of camps reporting session lengths of up to 2 weeks and 46% reporting session lengths of more than 2 weeks), illustrating the potential role of fatigue and/or lessened safety practices as staff familiarized themselves with the camp routine and their specific responsibilities. Fatigue associated with camp employment may also compromise employee performance, for example, to retain health and safety-related information learned during staff training (Garst, Gagnon, & Brawley, 2018).…”
mentioning
confidence: 99%